2004
DOI: 10.1111/j.1365-2672.2004.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extracellular endoxylanase, endoglucanase and peroxidase production by Streptomyces sp. F2621 isolated in Turkey

Abstract: Aims:  To determine the effect of environmental conditions on the production of extracellular lignocellulose‐degrading enzymes by Streptomyces sp. F2621 and to assess the potential use of these enzymes in the hydrolysis of lignocellulose material. Methods and Results:  The production of extracellular lignocellulose‐degrading enzymes, endoxylanase, endoglucanase and peroxidase during the growth of Streptomyces sp. F2621 in basal salts‐yeast extract medium containing different carbon sources and the effect of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 50 publications
(66 reference statements)
4
41
0
1
Order By: Relevance
“…Similarly, Streptomyces sp. F2621 (19) and S. albogriseous (20) also exhibited maximum endoglucanase activity at 26-30ºC with initial pH of 6.5-7.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Streptomyces sp. F2621 (19) and S. albogriseous (20) also exhibited maximum endoglucanase activity at 26-30ºC with initial pH of 6.5-7.0.…”
Section: Resultsmentioning
confidence: 99%
“…strain M7a & strain M7b (17), and Streptomyces sp. F2621 (19) have already reported to produce extracellular endoglucanase significantly in optimized culture media using cellulose powder as carbon source under shaking conditions. Culture conditions, therefore, play a prominent role on formation of endoglucanase from bacteria (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, though maximum growth was obtained on glucose, a readily metabolizable nutrient, basal expression of xyl1 and only trace amounts of XYL were produced by both races; however, although low, a higher XYL production was observed for race 1472, particularly early during incubation. A similar basal production of xylanase and endoglucanase (Sachslehner et al, 1998;Tuncer et al, 2004), pectinases (Hernández-Silva et al, 2007;Oyeleke et al, 2012;Riou et al, 1991) and cellulases (AcostaRodriguez et al, 2005;Carle-Urioste et al, 1997;Sharada et al, 2013) has been described in the fungi S. rolsfii, S. sclerotiorum and C. lindemuthianum, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In previous experiments, it was found that yeast extract is the preferred nitrogen source of Streptomyces strains (Gill et al, 2003;Lazim et al, 2009;Tuncer et al, 2004). However, every coin has two sides; it is also true for yeast extract in some Streptomyces strains (Niladevi et al, 2009).…”
Section: Validation Of the Optimized Conditionmentioning
confidence: 99%